Jalal al-Din Rumi and the National Albanian Poet ‘Naim Frasheri’ - Ziaee, Ali Akbar (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2012)
Naim Frashëri (1846-1900) is the most famous poet of the Albanian renaissance of the nineteenth century. He is nowadays widely considered to be the national poet of Albania. His role as a socio-political thinker in the liberation of Albania from the Ottoman conquest is of special significance. He was influenced by Rumi’s poems and influenced Albanian writers at the beginning of the twentieth century enormously. Many of his poems were set to music during his lifetime and were sung as folk songs in national celebrations in the religious ceremonies. In this article focus on Rumi’s influence on Naim Frasheri in the formation of Islamic Mystical literature in Albania.